The Effect of Kinesio Taping on Quadriceps Femoris Muscle Power and Strength in Non-Athlete Adult Males - Gunadi, Julia W; Limyati, Yenni; Ladi, Jeanny E; Clara, Stela; Sinaga, Hadrian M (Journal of Medicine and Health, 2017)
The use of Kinesio Taping has been reported to increase muscle power and strength,especially quadriceps femoris muscle, the great extensor of the leg. This research examines theeffect of Kinesio Taping on quadriceps femoris muscle power and strength in non-athlete adultmales. This research is quasi experimental design, involving 30 non-athlete adult males aged18-22 years old . Muscle power is examined by using Margaria-KalamenPower Test, andmuscle strength by using Isometric Leg Strength Test before, 20 minutes and 24 hours afterusing Kinesio Taping. The data is analyzed by using paired t test. The result shows that musclepower difference between 20 minutes and before using KinesioTaping (196,62±150,67) watt arelower than muscle power difference between 24 hours and before using KinesioTaping(247,31±139,88)watt (p value <0,01). The result also shows that muscle strength differencebetween 20 minutes and before using KinesioTaping (26,74±10,26)kg shows lower than musclestrength difference between 24 hours and before using KinesioTaping(30,26±9,99)kg(p value<0,01). KinesioTaping increases quadriceps femoris muscle power and strength 24 hours afterbetter than 20 minutes after using in non-athlete adult males.Keywords: Kinesio Taping, quadriceps femoris, muscle power, muscle strength